2010
DOI: 10.3390/d2030411
|View full text |Cite
|
Sign up to set email alerts
|

On the Biological and Genetic Diversity in Neospora caninum

Abstract: Neospora caninum is a parasite regarded a major cause of foetal loss in cattle. A key requirement to an understanding of the epidemiology and pathogenicity of N. caninum is knowledge of the biological characteristics of the species and the genetic diversity within it. Due to the broad intermediate host range of the species, worldwide geographical distribution and its capacity for sexual reproduction, significant biological and genetic differences might be expected to exist. N. caninum has now been isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 133 publications
(214 reference statements)
2
43
1
Order By: Relevance
“…Following the study by Payne and Ellis (1996), relating to the DNA region that codes for rRNA of N. caninum, several other studies have been published. However, in specifically analyzing the ITS-1 region, few studies have demonstrated nucleotide variations (AL-QASSAB et al, 2010). Similar findings were reported by Santos et al (2010), using sequences deposited in GenBank.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Following the study by Payne and Ellis (1996), relating to the DNA region that codes for rRNA of N. caninum, several other studies have been published. However, in specifically analyzing the ITS-1 region, few studies have demonstrated nucleotide variations (AL-QASSAB et al, 2010). Similar findings were reported by Santos et al (2010), using sequences deposited in GenBank.…”
Section: Discussionsupporting
confidence: 80%
“…However, the sequences obtained in this study referring to this region remained unchanged. This conservation of sequences probably occurred because of control over the mutagenic pressure, influenced by the immunity complex (AL-QASSAB et al, 2010). This conservation was reflected in the phylogenetic tree, which was characterized by presenting a single grouping of N. caninum, without distinguishing the geographical origin or type of host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neospora caninum is a protozoan parasite first identified in dogs but now mostly recognized as being associated with fetal death and abortion in midterm pregnant cattle (1). Although canids such as dogs and dingoes are known to be definitive hosts for this parasite (2), the main form of transmission among cattle is transplacental in utero from the dam to its fetus.…”
mentioning
confidence: 99%